2022
DOI: 10.1097/qad.0000000000003356
|View full text |Cite
|
Sign up to set email alerts
|

T-cell activation and B-cell interaction signatures in rectal tissues are associated with HIV replication in ex-vivo model of infection

Abstract: Objective: The rectal mucosa is a critical site of HIV vulnerability. We sought to identify transcriptomic features of rectal mucosal tissue prior to exposure associated with support or restriction of HIV replication.Design: Rectal tissue from HIV-negative cisgender men (n ¼ 57) underwent concurrent RNAseq transcriptomic analyses (two biopsies/participant) and challenge with HIV in the ex-vivo explant model of infection (three biopsies challenged/participant) as part of a larger cohort study to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Prior work [65,66] has also shown that asymptomatic rectal STI is associated with HIV seroconversion even in the setting of routine screening and treatment, which suggests that ongoing mucosal inflammation associated with asymptomatic STI could increase susceptibility to HIV. In our prior studies utilizing the explant challenge model to approximate HIV acquisition and early replication, we found increased p24 production was associated with differences in rectal mucosal cellular composition and the transcriptome [67]. Given the lack of immunologic effects of asymptomatic bacterial STI on either the cellular composition or the transcriptome in YMSM without HIV, the lack of differences in p24 production is not surprising and suggests that prior epidemiologic associations between asymptomatic STI and HIV acquisition may be confounded by behavioral factors.…”
Section: Plos Pathogensmentioning
confidence: 78%
See 1 more Smart Citation
“…Prior work [65,66] has also shown that asymptomatic rectal STI is associated with HIV seroconversion even in the setting of routine screening and treatment, which suggests that ongoing mucosal inflammation associated with asymptomatic STI could increase susceptibility to HIV. In our prior studies utilizing the explant challenge model to approximate HIV acquisition and early replication, we found increased p24 production was associated with differences in rectal mucosal cellular composition and the transcriptome [67]. Given the lack of immunologic effects of asymptomatic bacterial STI on either the cellular composition or the transcriptome in YMSM without HIV, the lack of differences in p24 production is not surprising and suggests that prior epidemiologic associations between asymptomatic STI and HIV acquisition may be confounded by behavioral factors.…”
Section: Plos Pathogensmentioning
confidence: 78%
“…Events were acquired on the LSR-Fortessa platform and analyzed with Flowjo software (Treestar Inc. CA). We used the gating strategies previously reported by our group for these analyses [60,67] and depicted in S3-S5 Figs.…”
Section: Blood and Rectal Mucosal Mononuclear Cell Phenotypingmentioning
confidence: 99%
“…Prior work [47, 48] has shown that asymptomatic rectal STI is associated with HIV seroconversion even in the setting of routine screening and treatment, which suggests that ongoing mucosal inflammation associated with asymptomatic STI could increase susceptibility to HIV. In our prior studies utilizing the explant challenge model to approximate HIV acquisition and early replication, we found increased p24 production was associated with differences in rectal mucosal cellular composition and the transcriptome[49]. Given the lack of immunologic effects of asymptomatic bacterial STI on either the cellular composition or the transcriptome in YMSM without HIV, the lack of differences in p24 production is not surprising and suggests that prior epidemiologic associations between asymptomatic STI and HIV acquisition may be confounded by behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Events were acquired on the LSR-Fortessa platform and analyzed with Flowjo software (Treestar Inc. CA). We used the gating strategies previously reported by our group for these analyses [49, 51].…”
Section: Methodsmentioning
confidence: 99%